2014
DOI: 10.4103/0976-237x.128663
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tranexamic acid mouthwash as an alternative for factor replacement in gingival bleeding during dental scaling in cases of hemophilia: A randomized clinical trial

Abstract: Objective:The objective of the following study is to evaluate freshly prepared tranexamic acid mouth wash (FTAMW) as an alternative to factor replacement therapy (FRT) in controlling gingival bleeding in hemophiliacs during dental scaling.Materials and Methods:Experimental treatment regime (ETR) involved saline transfusion followed by FTAMW and the control treatment regime (CTR) involved FRT followed by placebo mouthwash. A total of 22 hemophiliacs randomly received dental scaling under either CTR or ETR at tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
0
12
0
2
Order By: Relevance
“…It was initially introduced more than 40 years ago in cardiothoracic surgery and has shown application in controlling gynecologic hemorrhage and providing life-saving hemostasis in acute trauma. In addition to cardiothoracic 12 ; trauma 13 ; gynecological and obstetric 14,15 ; gastrointestinal 16 ; hepatic 12 ; urologic 17 ; and ear, nose, and throat surgeries, 12, 18 TXA has also been studied and used for diseases such as von Willebrand-factor deficiencies, 19 hemophilia, 20 and thrombocytopenia. 1,5,21 However, use in orthopedic surgery is not universal and remains subject to research.…”
mentioning
confidence: 99%
“…It was initially introduced more than 40 years ago in cardiothoracic surgery and has shown application in controlling gynecologic hemorrhage and providing life-saving hemostasis in acute trauma. In addition to cardiothoracic 12 ; trauma 13 ; gynecological and obstetric 14,15 ; gastrointestinal 16 ; hepatic 12 ; urologic 17 ; and ear, nose, and throat surgeries, 12, 18 TXA has also been studied and used for diseases such as von Willebrand-factor deficiencies, 19 hemophilia, 20 and thrombocytopenia. 1,5,21 However, use in orthopedic surgery is not universal and remains subject to research.…”
mentioning
confidence: 99%
“…An option for future hygienist procedures would be to provide the patient with TXA tablets but let them and the hygienist make a decision on whether or not it is required based on the amount of bleeding during and after the procedure. Two studies comparing the use of TXA with placebo during dental scaling in people with haemophilia reported that 38.5% and 36% of patients respectively did not bleed, regardless of whether TXA was given or a placebo [13,18] . The majority of patients in these studies had severe haemophilia, while the six patients interviewed for the current study all had mild bleeding disorders.…”
Section: Resultsmentioning
confidence: 99%
“…No conclusive evidence was found to advocate the efficacy of mouthwash compared with tablets, although TXA tablets are significantly cheaper than mouthwash [12] . Anderson et al suggest that tablets can be crushed by the patient and added to 10ml water to produce an oral solution that can be used as a mouthwash at a lower cost [10] , and the use of an oral solution prepared by patients using crushed tablets is reported by Nuvvula et al [13] . This method of administration is outside of Total: n=44…”
Section: Clinical Research Allison Greigmentioning
confidence: 99%
“…De un total de 115 publicaciones, solo 29 artículos cumplieron con el criterio de inclusión. De estos, 15 se utilizaron para identificar lo más reciente y relevante con respecto al tratamiento estomatológico de niños con hemofilia A (4,6,7,9,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Ello incluye adecuada evidencia y guías de práctica (tabla 1).…”
Section: Resultsunclassified